Electrical resistivity of FeSi alloy under high pressure - Nguyen, Thi Hong (Hue University Journal of Science: Natural Science, 2023)
The electrical resistivity of FeSi alloy under the influence of pressure is studied based on the Matthiessen's rule and saturation electrical resistivity model. Numerical calculations were conducted for FeSi up to a pressure of 100 GPa and compared with experimental data when possible. The results show that the electrical resistivity of the material diminishes gradually with pressure and saturates at high pressure. Furthermore, in this paper, we also investigated the effects of impurity concentration on the electrical resistivity of FeSi alloy. Our numerical calculations conducted for 40 and 80 Gpa pressures show that when the Si concentration is less than 20%, the electrical resistivity of the alloy increases rapidly and linearly with the Si concentration. Our electrical resistivity values are consistent with those of the recent experimental measurements.